Bureaucratic Innovation in Correctional Institutions in Riau Province - Herman, Herman; Wicaksono, Agung; Latif, Syahrul Akmal; Suriani, Lilis; Al Hafis, Raden Imam (Universitas Padjadjaran, 2025)
This study aims to analyze the bureaucratic innovations implemented at the Special Development Institution for Children (LPKA) in Pekanbaru City, Riau Province. The focus includes administrative, institutional, policy, and system innovations designed to improve the quality of public services in correctional institutions. A descriptive qualitative method was used with a case study approach. Data were collected through in-depth interviews, observation, and documentation, and analyzed inductively. The findings indicate that while various innovations have been introduced—such as the use of CCTV, digital-based services, and standardized operating procedures—the implementation remains suboptimal, particularly in administrative and system aspects. This study contributes to strengthening bureaucratic reform in correctional institutions and promotes the use of technology to enhance transparency and service efficiency. The findings offer practical implications for public service policy development in the correctional sector.